2011
DOI: 10.2478/v10183-011-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV-B radiations on the pigments of two Antarctic lichens of Schirmacher Oasis, East Antarctica

Abstract: Antarctic plants experience UV−B stress and for their survival they have been showing various adaptive strategies. The first line of defence is to screen UV−B radiation before it reaches the cell, then to minimize damage within the cells through other protective strategies, and finally to repair damage once it has occurred. A fifteen days experiment was designed to study lichen: Dermatocarpon sp. and Acarospora gwynnii under natural UV and below UV filter frames in the Indian Antarctic Station Maitri region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Whether or not the carotenoids pigments play a special role in the UV-C tolerance detected in both Trebouxia sp. photobionts is unclear, but previous research on lichen photobionts reported an increase in the carotenoid content after exposure to UV-B as a protective mechanism (Buffoni Hall 2002;Gautam et al 2011). Similar results were obtained with some microalgae species after exposures to UV-A (Salguero et al 2005;Mogedas et al 2009) and explained as an antioxidant-protective mechanism towards UV-B and UV-A.…”
Section: Discussionsupporting
confidence: 54%
“…Whether or not the carotenoids pigments play a special role in the UV-C tolerance detected in both Trebouxia sp. photobionts is unclear, but previous research on lichen photobionts reported an increase in the carotenoid content after exposure to UV-B as a protective mechanism (Buffoni Hall 2002;Gautam et al 2011). Similar results were obtained with some microalgae species after exposures to UV-A (Salguero et al 2005;Mogedas et al 2009) and explained as an antioxidant-protective mechanism towards UV-B and UV-A.…”
Section: Discussionsupporting
confidence: 54%
“…These metabolites screen solar radiation either by absorbance (parietin, melanins) or by reflectance (atranorin) to protect the photobiont against excessive photosynthetically active radiation (McEvoy et al 2007). Their concentration correlates with light exposure and is positively dependent on UV-B radiation as well (Gautam et al 2011). Many studies demonstrated that high doses of UV-B induced the synthesis of parietin, usnic acid, melanins, depsidones (lobaric acid, pannarin, etc.…”
Section: Introductionmentioning
confidence: 99%
“…NPQ increased slightly which could be attributed to early phase of activation of photoprotective processes in photosynthetic apparatus of symbiotic alga. Such a high resistance of U. antarctica to strong, but short-term UV-B treatment is not suprising since Antarctic lichens possess UV-B absorbing compounds that protect chlorophyll molecules from UV-B induced stress (Gautam et al 2011). The resistance might be related to a high, consti-tutive amount of UV-B absorbing compounds, umbilicaric acid and phenolic compounds in particular (Swanson et al 1996).…”
Section: Resultsmentioning
confidence: 99%